2013
DOI: 10.1007/s00247-013-2623-3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of hepatobiliary scintigraphy for differentiation of neonatal hepatitis from biliary atresia: systematic review and meta-analysis of the literature

Abstract: Hepatobiliary scintigraphy is an important diagnostic modality for work-up of neonatal cholestasis. Therefore, our objective was to evaluate the literature regarding the accuracy of hepatobiliary scintigraphy in differentiating biliary atresia from non-biliary atresia causes of cholestasis (collectively called neonatal hepatitis). Our search included Medline, SCOPUS and Google Scholar. Only studies using Tc-99 m-labeled immunodiacetic acid (IDA) derivatives were included. Overall, 81 studies were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 51 publications
1
43
0
1
Order By: Relevance
“…This observation has been demonstrated in multiple prior reports [15,16], and well-summarized in a recent metaanalysis that yielded a pooled sensitivity of 98.7% (range 98.1-99.2%) and specificity of 70.4% (range 68.5-72.2%) of a nondraining HIDA scan for BA [17]. Premedication with a drug that augments hepatocyte function and bile flow (such as phenobarbital) may improve specificity by increasing the likelihood of drainage in patients with conditions such as neonatal hepatitis, but we did not see a significant effect from premedication in our study; further work is necessary to assess the utility of premedication for HIDA, as currently it represents the greatest contributor to diagnostic delay in the algorithm (median 5 days).…”
Section: Discussionsupporting
confidence: 65%
“…This observation has been demonstrated in multiple prior reports [15,16], and well-summarized in a recent metaanalysis that yielded a pooled sensitivity of 98.7% (range 98.1-99.2%) and specificity of 70.4% (range 68.5-72.2%) of a nondraining HIDA scan for BA [17]. Premedication with a drug that augments hepatocyte function and bile flow (such as phenobarbital) may improve specificity by increasing the likelihood of drainage in patients with conditions such as neonatal hepatitis, but we did not see a significant effect from premedication in our study; further work is necessary to assess the utility of premedication for HIDA, as currently it represents the greatest contributor to diagnostic delay in the algorithm (median 5 days).…”
Section: Discussionsupporting
confidence: 65%
“…A recent large meta-analysis showed a pooled sensitivity of 98.7% and specificity of 70.4% for this imaging test in differentiating biliary atresia from neonatal hepatitis [17]. False- Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Histological findings of biliary atresia include intrahepatic bile ductular proliferation, cholangiolar bile plugs, and liver fibrosis [17]. A study by Rastogi et al [18] showed that the sensitivity and specificity of percutaneous liver biopsy are both approximately 88%.…”
Section: Discussionmentioning
confidence: 98%
“…However, in the background of elevated bilirubin levels and likely deranged liver function, ability to take up the agent may be compromised. To overcome this, cholegogues such as Ursodeoxy cholic acid, Phenobarbitone, Phenytoin are used as pre-treatment agents, to ensure adequate “priming”[53]. …”
Section: Investigationsmentioning
confidence: 99%